2020
DOI: 10.3390/toxins12030160
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Mycotoxins in Fish Feed and Its Effects: A Review

Abstract: Plant-based ingredients have been successfully replacing fishmeal in finished fish feeds. However, using crops in feeds results in an increased risk of contamination by fungi and mycotoxins and a higher incidence of mycotoxicosis in fish. This might decrease aquaculture’s productivity as mycotoxicosis generally result in decreased body weight, growth impairment and higher rates of disease and mortality in fish. Additionally, some mycotoxins might accumulate in the fish musculature. As such, fish consumption mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 118 publications
2
63
0
8
Order By: Relevance
“…Organ-specific effects, and even more importantly subclinical effects such as the impairment of the intestinal integrity and effects on the intestinal microbiome are of increasing concerns, as they may occur already at low [ 43 , 44 ]. Great strides have been made in the assessment and management of fungal metabolite risks to human and animal health (monitoring programs in Europe to help protect public health from the risks posed by the major mycotoxins found in foods and feeds, including TCT) [ 43 , 44 , 46 , 47 , 48 , 49 ]. There are also strong indications that climate change will change the spatial and temporal distribution patterns of TCT production.…”
Section: Trichothecenes In Food and Feedmentioning
confidence: 99%
“…Organ-specific effects, and even more importantly subclinical effects such as the impairment of the intestinal integrity and effects on the intestinal microbiome are of increasing concerns, as they may occur already at low [ 43 , 44 ]. Great strides have been made in the assessment and management of fungal metabolite risks to human and animal health (monitoring programs in Europe to help protect public health from the risks posed by the major mycotoxins found in foods and feeds, including TCT) [ 43 , 44 , 46 , 47 , 48 , 49 ]. There are also strong indications that climate change will change the spatial and temporal distribution patterns of TCT production.…”
Section: Trichothecenes In Food and Feedmentioning
confidence: 99%
“…One of the first indications of a chronic mycotoxicosis is growth depression, which can result from reduced feed intake, impaired nutrient utilization and changes in feed quality or toxicity (Bryden, 2012). Among the animals, poultry, pigs and aquatic vertebrates are very sensitive to mycotoxins (Oliveira and Vasconcelos, 2020).…”
Section: Impact Of Mycotoxins On Animal Health and Productivitymentioning
confidence: 99%
“…However, fishmeal, an important ingredient of fish feeds, will be scarce in the future. Therefore, cereals are often used to replace at least a part of the fishmeal in fish feeds, leading to increased mycotoxin contamination [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of gpx4a and gpx4b genes showed down-regulation, followed by up-regulation irrespective of the dose. There is little information about the effect of STC on lipid peroxidation and antioxidant defense in fish [ 2 ]; however, in vivo studies performed on rats and chickens showed an increase in CAT activity in rats [ 40 , 41 ] and GPx activity in chicken [ 42 ]. Our previous short-term STC exposure study with common carp showed that different doses (1 mg, 2 mg, and 4 mg STC /kg feed) have a moderate effect on lipid peroxidation parameters in the liver, and only at low dose.…”
Section: Introductionmentioning
confidence: 99%